Composing leadership education by institutional type. Issue 171 (18th October 2021) - Whitney, Rich; Collins, Jasmine D.
Abstract: This issue highlights leadership development approaches within institutional contexts that have not been well represented in leadership education research. As the first publication in the field to address racial equity through the lens of institutional type in this way, authors were given the challenging task of laying a conceptual, historical, and empirical foundation for readers in the absence of a robust body of literature. What follows is a synthesis of themes observed across each of the articles, concluding with implications for inclusive leadership research and practice.